This is super elementary, so I apologize in advanced:

$$\frac{4}{3} - \frac{8}{9} + \frac{16}{27} - \frac{32}{81} + \ldots$$

Does this series converge or diverge?

I am trying to find a pattern but neither taking out $4/3$ or $4$ seems to work any suggestions would be greatly appreciated. I am sorry again for being so elementary. I am not in this class just trying to refresh myself with algebra for tutoring

  • 2
    $\begingroup$ Is that it or is it supposed to have more than 4 terms? $\endgroup$ – user228113 Apr 30 '15 at 20:28
  • 1
    $\begingroup$ Do you mean $$\sum_{n=2}^{\infty }\frac{(-2)^n}{3^{n-1}}$$ $\endgroup$ – E.H.E Apr 30 '15 at 20:29
  • $\begingroup$ Try writing the denominators as powers of 3 and the numerators as powers of 2. The pattern will become super obvious. $\endgroup$ – John Joy Apr 30 '15 at 20:36
  • $\begingroup$ Obvious now, thanks and sorry for the trivial post $\endgroup$ – Wolfy Apr 30 '15 at 20:44

The series is converging.

As you can see, the terms are given by $x_n=(-1)^{n-1}\frac{2^{n+1}}{3^n}=(-1)^{n-1}\cdot2\cdot (\frac{2}{3})^n$ where $n\geq1$

Now, we have


$\lim_{n\to\infty} |x_n|=\lim_{n\to\infty}2\cdot (\frac{2}{3})^n=0$ since $\frac{2}{3}<1$

Thus, by the alternating series test, the series converges.

For the sake of completion, put $\sum x_n=\sum_{n=1}^\infty -2\cdot(\frac{-2}{3})^n =-2\sum_{n=1}^\infty (\frac{-2}{3})^n=-2(-\frac{2}{5})=\frac{4}{5}$



Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.